Exposure to Ammonia Concentration from the Processing of Crumb Rubber on Environmental Quality: A Review - Komarudin, Nurul Amri; Tarigan, Elsera Br; Shafiyuddin Hilmi, Yahya; Velasco, Ashemir B (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2022)
Nowadays, processed natural rubber products such as crumb rubber have become the demands of global consumers who are oriented towards export markets. Therefore, the economic impact is felt more, but there are still other consequences. The consequences are not only economically beneficial but can also be detrimental to environmental conditions. The process of making natural rubber into crumb rubber causes a negative impact by means of air pollution in the form of odour, which is rarely noticed. The purposes of this study were to analyse the ammonia concentration resulting from the processing of natural rubber into crumb rubber, and to identify the impact of ammonia contamination on the environment, particularly human health. This research was conducted using a review method with the help of colandr machine learning. The results of the review show that the concentration of ammonia produced from the processing of natural rubber into crumb rubber in Indonesia has passed the specified quality standard threshold. It is found to impact the environment such as damage to aquatic ecosystems and air quality, as well as effects on human health such as respiratory problems.